A Narrative Review on the Natural Remedies Used in the Prevention and Symptomatic Treatment of Constipation in the Middle East - Sareh Dortaj * (Lorestan University of Medical Sciences, 2022)
Constipation is a common issue in developed and developing countries. On account of the multifactorial nature of this bowel problem, it has been indicated that current conventional treatments have limited efficacy and a higher incidence of side effects. This article aims to review various natural remedies that have proved to be effective in the prevention and/or treatment of constipation and is an attempt to provide a framework for a better understanding of the pharmacology of these herbs. Treatments were identified from electronic databases such as ISI Web of Knowledge, PubMed, and Scopus. Out of 103 studies found via electronic search, 49 studies fulfilled the eligibility criteria and were included in this review. Anthraquinone, saponin, and fiber-rich plants may increase the frequency of defecation through their bulking and/or stimulant laxative effects. The intake of some herbs or their isolated purgative active constituents can be useful in constipated patients. However, if the patient has tried natural remedies for more than three days without success, it is preferred to refer to a physician to know the underlying cause of constipation.